(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This study aims to identify the role of school psychological counselors during crises from the perspective of principals of basic education schools (second cycle) in the city of Lattakia. To achieve this objective, a questionnaire was developed regarding the role of school psychological counselors during crises from the perspective of the same principals. The research sample consisted of 70 principals (male and female), selected through purposive sampling. The researcher adopted the descriptive method. The findings indicate that the degree of appreciation of the role of school psychological counselors during crises, from the perspective of basic education school principals (second cycle) in Lattakia, was at a medium level. Furthermore, the results revealed a statistically significant difference between the mean rank responses of the sample members on the questionnaire based on the variable (attending a psychological support course vs. not attending a psychological support course), in favor of principals who had attended a psychological support course. Additionally, a statistically significant difference was found between the mean rank responses based on the variable of educational qualification (university degree vs. diploma in educational qualification), in favor of principals holding a diploma in educational qualification.